2015
DOI: 10.1007/s11661-015-2997-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Intermetallic Phases in Fe-rich Fe-Cr-Ni-Mo Alloys

Abstract: Understanding the thermal stability of intermetallic phases in Fe-rich Fe-Cr-Ni-Mo alloys is critical to alloy design and application of Mo-containing austenitic steels. Coupled with thermodynamic modeling, the thermal stability of intermetallic Chi and Laves phases in two Fe-CrNi-Mo alloys was investigated at 1273 K, 1123 K, and 973 K (1000°C, 850°C, and 700°C) for different annealing times. The morphologies, compositions, and crystal structures of the precipitates of the intermetallic phases were carefully e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…To study the phase transformation between the χ and Laves phases, a high-Mo-content model alloy was designed to have a composition of Fe-13.2Cr-14.2Mo-12.9Ni in weight percentage (wt%), using computational thermodynamics with an optimized thermodynamic database [10]. The calculated phase amount in the alloy as a function of temperature is shown in Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…To study the phase transformation between the χ and Laves phases, a high-Mo-content model alloy was designed to have a composition of Fe-13.2Cr-14.2Mo-12.9Ni in weight percentage (wt%), using computational thermodynamics with an optimized thermodynamic database [10]. The calculated phase amount in the alloy as a function of temperature is shown in Fig.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Laves phase is also an intermetallic phase with hexagonal crystal structure and it usually consists of iron, molybdenum, titanium, niobium, silicon, chromium and nickel [26,27]. In niobium containing steels, Laves phase is detrimental for the creep properties because it promotes formation of M 6 C [17].…”
Section: Precipitationmentioning
confidence: 99%
“…But in high nickel austenitic stainless steels with tungsten, it is found that the formation of Laves phase in the grain boundaries may improve the creep strength [28]. Generally Laves phase is found dispersed inside the grains, but sometimes also at grain boundaries after long time high-temperature exposure between 600 • C and 1000 • C. In niobium and tungsten containing austenitic stainless steels it can form as Fe 2 Nb and/or Fe 2 W after ageing around 600 • C and 800 • C [21,26,27].…”
Section: Precipitationmentioning
confidence: 99%
“…Laves phase has a hexagonal structure, it consists mostly of iron, molybdenum, an intermediate content of chromium and nickel [51,53,57] and a small amount of manganese, silicon, titanium and niobium [53]. It precipitates at intragranular sites and occasionally at GBs, often in small amounts, after 1000 hours ageing at temperatures between 600…”
Section: Carbides and Nitridesmentioning
confidence: 99%
“…X-phase has a body centred cubic (BCC) structure, it is rich in iron, chromium and molybdenum [13,57]. It forms at GBs and intragranularly, where it nucleate on dislocations, after 5000 hours at temperatures between 700…”
Section: Carbides and Nitridesmentioning
confidence: 99%